2021
DOI: 10.1016/j.neuint.2021.105039
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation during human cortical development: Seq-ing answers from the brain to the organoid

Abstract: Epigenetic regulation plays an important role in controlling gene expression during complex processes, such as development of the human brain. Mutations in genes encoding chromatin modifying proteins and in the non-protein coding sequences of the genome can potentially alter transcription factor binding or chromatin accessibility. Such mutations can frequently cause neurodevelopmental disorders, therefore understanding how epigenetic regulation shapes brain development is of particular interest. While epigenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 104 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…Although ChIP-seq is a widely used method to evaluate global active and repressed chromatin states, it is limited by low signal-to-noise ratios and is not compatible with low cellular input–a potentially significant challenge for organoid applications ( Lewis et al, 2021 ). However, newer chromatin mapping methods such as CUT&RUN and CUT&Tag can be combined with scRNA-seq to target and profile specific chromatin signatures with single cell resolution ( Kaya-Okur et al, 2019 ; Yu et al, 2022 ).…”
Section: Genomics Technologies To Study Molecular Features Of Auts2 D...mentioning
confidence: 99%
“…Although ChIP-seq is a widely used method to evaluate global active and repressed chromatin states, it is limited by low signal-to-noise ratios and is not compatible with low cellular input–a potentially significant challenge for organoid applications ( Lewis et al, 2021 ). However, newer chromatin mapping methods such as CUT&RUN and CUT&Tag can be combined with scRNA-seq to target and profile specific chromatin signatures with single cell resolution ( Kaya-Okur et al, 2019 ; Yu et al, 2022 ).…”
Section: Genomics Technologies To Study Molecular Features Of Auts2 D...mentioning
confidence: 99%
“…In addition, certain aspects of PcG regulation may be species-specific, requiring investigation in human model systems (E. M. A. Lewis et al, 2021;van de Werken et al, 2014). Examining PcG function in the context of human tissues, specifically during human neurogenesis, will require new experimental approaches.…”
Section: Polycomb Group Proteinsmentioning
confidence: 99%
“…The development of human iPSCs and advanced protocols for generation of brain organoids has drastically changed possibilities for neurodevelopmental research. Important aspects of early human brain development (Kelava & Lancaster, 2016; Mora‐Bermudez et al., 2016; Pollen et al., 2019), including cell morphology and tissue structure as well as gene expression patterns (Camp et al., 2015) and overall epigenomic landscape (Amiri et al., 2018; E. M. A. Lewis et al., 2021; Trevino et al., 2020) are recapitulated in these 3D in vitro models. There are various approaches on how to examine PcG activity and function in these advanced 3D cell culture systems as well as ex vivo in human primary tissue samples, some of which we will highlight here (Figure 6).…”
Section: Experimental Approaches To Study Pcg Regulation In Human Cor...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several recent reports have suggested that phenotypic variation induced by PrEE can extend several generations ( Govorko et al, 2012 ; Gangisetty et al, 2020 ), likely via epigenetic mechanisms ( Chastain and Sarkar, 2017 ). Because precise epigenetic regulation, or the control of gene expression not related to changes in DNA sequence, is also crucial for complex development of the neocortex ( Adam and Harwell, 2020 ; Lewis et al, 2021 ) as well as how PrEE induces widespread epigenetic dysregulation in the brain ( Subbana et al, 2014 ; Öztürk et al, 2017 ), the notion that underlying epigenetic mechanisms may be driving transgenerational FASD phenotypes represents an attractive hypothesis.…”
Section: Introductionmentioning
confidence: 99%